Interorganizational Context When Implementing Multisector Partnered Programs: A Qualitative Analysis of Veteran Directed Care. Issue 8 (16th November 2020) - Clary, Alecia S.; Perry, Kathleen R.; Edwards-Orr, Merle; Miech, Edward J.; VanHoutven, Courtney; Rudolph, James L.; Thomas, Kali S.; Sperber, Nina
ABSTRACT: As the number of Veterans enrolled in the Veterans Health Administration (VHA) and at risk for needing Long Term Services and Supports increases, VHA is shifting from institutional to Home and Community Based Services, such as the Veteran-Directed Care (VDC) program. VDC is a multi-sector program implemented as a collaboration between individual VHA medical centers (VAMCs) and Aging and Disability Network Agencies (ADNAs), entities that sit outside the VHA. Factors that affect establishment of effective multi-sector programs such as VDC are poorly understood, limiting ability to effectively deliver and scale programs. We conducted a qualitative study to describe factors affecting the interorganizational implementation context of VDC. Using constructs from the Consolidated Framework for Implementation Research (CFIR), we interviewed VDC coordinators from seven different VAMC-ADNA partnerships that initiated the VDC program between 2017 and 2018. We identified eight CFIR determinants which manifested similarly for the VAMCs and ADNAs: evidence strength and quality, relative advantage, adaptability, tension for change, access to knowledge and information, self-efficacy; engaging, and champions. We identified three CFIR determinants that varied dramatically across VAMCs and ADNAs: available resources, implementation climate, and relative priority. Our results suggest that interorganizational context plays a critical and dynamic role within multi-sector collaborations.